Peningkatan keterampilan menulis deskripsi melalui strategi directed writing activity (dwa) siswa kelas IV sekolah dasar - Muhammad Rizki Darmawan; Rukayah Rukayah; Tri Budiharto (Universitas Sebelas Maret, 2023)
Abstract. Description writing skills are language skills that are very important for students. The skill of writing descriptions is closely related to the ability to produce ideas or ideas into writing to compete globally. The purpose of this study is to improve description writing skills using the Directed Writing Activity (DWA) strategy. This type of research, classroom action research with the application of two cycles and consists of two meetings. Each consists of four steps, namely the planning cycle, action, observation and reflection. Data was collected using several techniques such as observation, interviews, documentation and test writing descriptions. Interactive models are used to analyze data. Assessment in the study showed that the teacher's performance and writing skills of the students' description improved continuously. Referring to the results, it can be concluded that through the directed writing activity (DWA) strategy improves the writing skills of grade IV students' descriptions.Keywords: description writing, Directed Writing Activity (DWA), elementary school